Patient-reported quality of life after tisagenlecleucel infusion in children and young adults with relapsed or refractory B-cell acute lymphoblastic leukaemia: a global, single-arm, phase 2 trial. Issue 12 (December 2019) - Laetsch, Theodore W; Myers, Gary Douglas; Baruchel, André; Dietz, Andrew C; Pulsipher, Michael A; Bittencourt, Henrique; Buechner, Jochen; De Moerloose, Barbara; Davis, Kara L; Nemecek, Eneida; Driscoll, Timothy; Mechinaud, Francoise; et al.
Summary: Background: The ELIANA trial showed that 61 (81%) of 75 paediatric and young adult patients with relapsed or refractory B-cell acute lymphoblastic leukaemia achieved overall remission after treatment with tisagenlecleucel, a chimeric antigen receptor targeted against the CD19 antigen. We aimed to evaluate patient-reported quality of life in these patients before and after tisagenlecleucel infusion. Methods: ELIANA, a global, single-arm, open-label, phase 2 trial, was done in 25 hospitals across Australia, Austria, Belgium, Canada, France, Germany, Italy, Japan, Norway, Spain, and the USA. Patients with B-cell acute lymphoblastic leukaemia aged at least 3 years at the time of screening and 21 years or younger at the time of initial diagnosis who were in second or greater bone marrow relapse, chemorefractory, relapsed after allogeneic stem-cell transplantation, or were otherwise ineligible for allogeneic stem-cell transplantation were enrolled. Patients received a single intravenous administration of a target dose of 0·2–5 × 10 6 transduced viable T cells per kg for patients weighing 50 kg or less or 0·1–2·5 × 10 8 transduced viable T cells for patients weighing more than 50 kg. The primary outcome, reported previously, was the proportion of patients who achieved remission. A prespecified secondary endpoint, reported here, was patient-reported quality of life measured with the Pediatric Quality of Life Inventory (PedsQL) and European Quality of Life-5 Dimensions questionnaire (EQ-5D). Patients completed the questionnaires at baseline, day 28, and months 3, 6, 9, and 12 after treatment. The data collected were summarised using descriptive statistics and post-hoc mixed models for repeated measures. Change from baseline response profiles were illustrated with cumulative distribution function plots. The proportion of patients achieving the minimal clinically important difference and normative mean value were reported. Analysis was per protocol. This study is registered with ClinicalTrials.gov, NCT02435849 . Findings: Between April 8, 2015, and April 25, 2017, 107 patients were screened, 92 were enrolled, and 75 received tisagenlecleucel. 58 patients aged 8–23 years were included in the analysis of quality of life. At baseline, 50 (86%) patients had completed the PedsQL questionnaire and 48 (83%) had completed the EQ-5D VAS. Improvements in patient-reported quality-of-life scores were observed for all measures at month 3 after tisagenlecleucel infusion (mean change from baseline to month 3 was 13·3 [95% CI 8·9–17·6] for the PedsQL total score and 16·8 [9·4–24·3] for the EQ-5D visual analogue scale). 30 (81%) of 37 patients achieved the minimal clinically important difference at month 3 for the PedsQL total score and 24 (67%) of 36 patients achieved this for the EQ-5D visual analogue scale. Interpretation: These findings, along with the activity and safety results of ELIANA, suggest a favourable benefit–risk profile of tisagenlecleucel in the treatment of paediatric and young adult patients with relapsed or refractory B-cell acute lymphoblastic leukaemia. Funding: Novartis.